The Quality of Water of the Downstream of the Siak River, Riau Province, Based on Tidal Condition - Yuliati Yuliati; Etty Riani; Bambang Pramudya N. Pramudya N.; Achmad Fahrudin (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
The quality of water in a river is affected by its natural condition and pollutant input originated from activities conducted around the river. In the Siak river, however, the black water effect influences thedistribution of the pollutant in general. To understand the quality of water in the black water affected by an area, a study was conducted from December 2015 to July 2016. The water was sampled during lowand high tides, in 8 sampling sites that were distributed along the river, from the mouth of the river in Siak Sri Indrapura Regency to upstream in Palas Village, Kampar Regency (around 180 km from the mouth ofthe river). The results showed that in the downstream of the Siak river, the quality of water during the low and high tides was worse than the 3rd Class Water Quality Standard issued by the Government Regulation (GR No. 82 / 2001) except for the concentration of nitrate, total coliform, Hg, oil and fat. The BOD was 14-39.2 mg/L (the high tide) and 17-45.6 mg/L (the low tide), COD was 51.76-80.62 mg/L (thehigh tide) and 51.76-69.12 mg/L (the low tide), NH3-N was 0.03-1.09 mg/L (the high tide) and 0.03-0.92 mg/L (the low tide), while the NO2-N was 0.13-0.17 mg/L (the high tide) and 0.13-0.22 mg/L (the low tide). Based on the Storet Index, the water of the downstream in the Siak river during the low and the high tide can be categorized as heavily polluted (score -52 to -70), and it tends to decline during the high tide.